A cross-sectional study: a breathomics based pulmonary tuberculosis detection method - Liang Fu; Lei Wang; Haibo Wang; Min Yang; Qianting Yang; Yi Lin; Shanyi Guan; Yongcong Deng; Lei Liu; Qingyun Li; Mengqi He; Peize Zhang; et al. (BMC Infectious Diseases, 2023)
Key messages What is already known on this topic—Breath VOC analysis is a potential technology for PTB detection. However, it is still desirable for a real-time, robust, accurate, and simple breath analysis platform for clinical application. What this study adds—An online breath detection for PTB was proposed and demonstrated with high sensitivity and specificity in a large clinical cohort. How this study might affect research, practice, or policy—This study may promote the application of breath detection in clinical TB detection and related biomarker studies.